2024
DOI: 10.1002/anie.202318919
|View full text |Cite
|
Sign up to set email alerts
|

Step‐growth Polymerization of Aziridines with Elemental Sulfur: Easy Access to Linear Polysulfides and Their Use as Recyclable Adhesives

Huishan Huang,
Shuojia Zheng,
Jiye Luo
et al.

Abstract: The bulk radical polymerization of bis(aziridine) with molten elemental sulfur resulted in brittle, cross‐linked polymers. However, when the bis(aziridine) was treated with elemental sulfur in the presence of an organobase, the ring‐opening reaction of aziridine with oligosulfide anions occurred, leading to the formation of linear polymers by step‐growth polymerization. These newly synthesized polymers possess repeating units containing a sulfonamide or amide functional moiety and oligosulfide bonds with an av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Very recently, we found that N-tosyl aziridine can undergo a radical ring-opening reaction with molten elemental sulfur but with no regioselectivity. 45 The inverse vulcanization of bis(N-sulfonyl aziridine) gave brittle polymers with poor mechanical properties. Despite the unsuccess of producing high-performance polymers, the high reactivity of the aziridine may contribute to the incorporation of functional moieties into the polysulfide materials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Very recently, we found that N-tosyl aziridine can undergo a radical ring-opening reaction with molten elemental sulfur but with no regioselectivity. 45 The inverse vulcanization of bis(N-sulfonyl aziridine) gave brittle polymers with poor mechanical properties. Despite the unsuccess of producing high-performance polymers, the high reactivity of the aziridine may contribute to the incorporation of functional moieties into the polysulfide materials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Very recently, we found that N -tosyl aziridine can undergo a radical ring-opening reaction with molten elemental sulfur but with no regioselectivity . The inverse vulcanization of bis­( N -sulfonyl aziridine) gave brittle polymers with poor mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations